Motion Graphic Animation Video Media for Class VII Social Studies Subjects - Hajizah, Nurul; I Made Tegeh (Universitas Pendidikan Ganesha, 2023)
This research is motivated by the need for more innovation in developing learning media to support student learning outcomes. The purpose of this research is to describe the process of developing learning motion graphic animation video media and analyse the validity of the development of learning motion graphic animation video media in social studies class VII. This research is included in the type of development research using the ADDIE model as a guide in the development process. The subjects involved in this study were one learning content expert, one learning design expert, one learning media expert, and product trial subjects consisting of 3 students for individual trials and six students for small group trials. The methods used in collecting data in this study were questionnaires and tests. Data analysis was carried out through quantitative descriptive analysis. The results of the validity test of the learning motion graphic animation video media were declared valid based on the assessment of experts and individual and small group tests. So that the product can be declared valid, based on the results of the evaluation, the learning motion graphic animation video media has excellent qualifications and is feasible to be applied in the learning process in class VII social studies subjects. The results of this study have implications for increasing student motivation and interest in learning, as well as improving skills in using technology so that it can support student activities in learning.